W. E. Vine's New Testament word pictures : a commentary drawn from the original languages.: a commentary drawn from the original languages. Hebrews to Revelations / (2022) - Vine, W. E (William Edwy), 1873-1949; Bruce, F. F (Frederick Fyvie), 1910-1990
No abstract available